2020
DOI: 10.1093/ptj/pzaa224
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Flow Restriction Training for a Person With Primary Progressive Multiple Sclerosis: A Case Report

Abstract: Objective Blood flow restriction (BFR) training, in which an inflatable cuff partially occludes blood flow around the proximal portion of a limb, coupled with low-intensity resistance training (LIRT) has resulted in gains comparable to traditional progressive resistive exercise in healthy populations. The use of BFR with LIRT may enable people with multiple sclerosis (MS) to improve strength without an increase in fatigue. The purpose of this case report is to describe the use of a BFR/LIRT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…An additional aspect to take into account, apart from the favorable results, are the adverse effects that BFR may have. None of the articles in our review found any that were in agreement with the majority of the scientific literature [ 17 , 18 , 20 ]. Nevertheless, one study found adverse effects.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…An additional aspect to take into account, apart from the favorable results, are the adverse effects that BFR may have. None of the articles in our review found any that were in agreement with the majority of the scientific literature [ 17 , 18 , 20 ]. Nevertheless, one study found adverse effects.…”
Section: Discussionsupporting
confidence: 51%
“…There are several therapeutic possibilities, including conservative treatment, with the goal of enhancing daily activities, avoiding deformities, preserving joint motion, relieving pain, and reducing muscle tone [ 14 ]. While most of the investigations on BFR training have focused on healthy populations [ 15 , 16 ], some case or observational studies have been performed on BFR in patients with neurological problems, such as Parkinson’s disease [ 17 , 18 ], multiple sclerosis [ 19 , 20 , 21 , 22 ], spinal cord injury [ 7 ] and stroke [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that aquatic exercise is superior to other interventions in improving functional walking ability. The mechanism by which aquatic exercise improves TUG can be explained in several ways: (1) The presence of water resistance allows the patient to perform exercises more slowly than land-based exercises, resulting in an increased weight-bearing time on the lower limbs; in addition, the patient’s torso is subjected to a certain amount of water pressure in the aquatic environment [ 59 ] which has a similar effect on the skeletal muscles as blood flow restriction training [ 60 ] (a training modality that was shown to have a significant effect on increasing muscle strength) [ 61 ]. (2) When exercising in the water, hydrostatic force causes the blood and lymphatic fluid to move up the torso, and combined with the gravitational offload and hydrostatic effect of the water, it increases the amount of blood circulating from the periphery to the center, resulting in an increase in the end-diastolic volume of the heart and thus an increase in cardiac output [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring appropriate prescreening, methodology and application of MBFR is of utmost importance whether used with RT, aerobic training or in a passive manner (for a review see [17]). Some laboratories have successfully implemented MBFR interventions for individuals with Parkinson disease [65], chronic kidney disease [66,67] and multiple sclerosis [57,68], as well as following spinal cord injury [59], with results appearing to suggest the technique is tolerated and possibly beneficial, however evidence is still lacking for other diseased states. Although limited evidence exists for the use of MBFR in clinical populations, a risk stratification model has been proposed to identify risk factors prior to participating in exercise programs utilizing MBFR [69].…”
Section: Safety Considerationsmentioning
confidence: 99%